Life skills and sexual risk behaviors among adolescents in Indonesia: A cross-sectional survey - Ati Surya Mediawati; Iyus Yosep; Ai Mardhiyah (Belitung Nursing Journal, 2022)
Background:  Adolescents require life skills and individual and interpersonal abilities to grow into adults with a healthy lifestyle. Although the majority of the literature indicates that life skills increase teenagers’ cognitive, social, and emotional abilities, there is a lack of data correlating life skills to sexual risk behaviors. Objective: This study aimed to examine the relationship between life skills and sexual risk behaviors among adolescents aged 15–19 in Bandung, Indonesia. Methods: This study was conducted using a cross-sectional survey of 480 adolescents from April to May 2021. A representative sample was drawn from the students aged 15–19 years. The participants were selected using simple random sampling generated by computer software. Life Skill Training Questionnaire High School (LSTQ-HS) and sexual risk behaviors instruments were used for data collection, and logistic regression was used for data analysis. Results: From a total of 480 respondents, about 23.3% had masturbation experience, 25.8% had petting experience, 8.3% had sexual intercourse, 5% had sex before 18 years of age, and 4.2% had oral sex experience. Sexual risky behaviors were associated with unfavorable refusal skill (AOR = 6.46, 95% CI = 2.37, 17.53), assertiveness skill (AOR = 3.51, 95% CI = 1.32, 4.33), problem-solving skill (AOR = 5.35, 95% CI = 2.88, 11.39), and self-control skill (AOR = 7.31, 95% CI = 2.79, 17.24). Conclusion:  Life skills are important protective aspects for those who engage in sexually risky behavior. Considering the study findings, tailored life skills programs are critical for adolescent wellbeing and risk reduction. Nurses who take a proactive role in providing sexual and reproductive health services may provide more accurate information and provide early screening and assessment for sexual and reproductive behavior to reduce risky sexual behavior among adolescents. Schools are also encouraged to work with local health departments to conduct sexual education counseling programs.